KNOWLEDGE OF ISLAMIC EDUCATION TEACHER IN IMPLEMENTING TEACHING OF HIGHER ORDER THINKING SKILLS (HOTs) - Muhammad Talhah Ajmain@Jima’ain; Aminudin Hehsan; Juhazren Junaidi; Ahmad Marzuki Mohamad (Journal of Islamic, Social, Economics and Development, 2019)
Islamic Education teachers play a big role in educating generations. Thinking skills are very important in directing students so that they can learn well and apply it. This study is a survey conducted on Islamic Education teachers in secondary schools in Selangor for the purpose of identifying the level of understanding of Islamic Education teachers towards the application of higher order thinking skills (HOTs) in teaching and facilitating (PdPc) of Islamic Education. The questionnaire was used as the main instrument in this study. A total of 117 Islamic Education teachers were involved as respondents in the study. Data obtained from the questionnaires distributed were analyzed using IBM Statistical Package which involved mean score, standard deviation, percentage, and frequency. The findings of the previous study to all teachers showed that the level of knowledeg of teachers towards HOTs was moderate. However, the findings in this study indicate that the level of knowledge of the Islamic Education teacher is at a high level with a score of (min = 4.05). This study is expected to assist the school, researcher and the Islamic and Moral Education Curriculum Division, Ministry of Education to implement improvements. Furthermore, it provides numerous plans to enhance teachers' knowledge and skills, in particular, the Islamic Education teachers in order to enhance the success of the application of Higher Order Thinking skills (HOTs) in Islamic Education subject to meet the 21st Century National Education System (SPN21). Further efforts can help improve the quality of teachers in implementing new skills to be applied in teaching and facilitating (PdPc).